Play and Social Skills for Children with Autism Spectrum Disorder - Charlop, Marjorie H. (Evidence-Based Practices in Behavioral Health,, 2018)
This book discusses the deficits in the development and presentation of play behavior and social skills that are considered central characteristics of autism spectrum disorder (ASD). The book explains why play provides an important context for social interactions and how its absence can further exacerbate social deficits over time. It highlights the critical roles of social skills in development, and the social, cognitive, communication, and motor components of play. Chapters offer conceptually and empirically sound play and social skills interventions for children with ASD. Play activities using diverse materials and including interactions with peers and parents are designed to promote positive, effective social behaviors and encourage continued development. The book provides unique strategies that can be tailored to fit individual children's strengths and deficits. Topics featured in this book include: Naturalistic Teaching Strategies (NaTS) for developing play and social skills. Teaching play and social skills with video modeling. Peer-mediated intervention (PMI) strategies that promote positive social interactions between children with ASD and their peers. Visual Activity Schedules and Scripts. Parent-implemented play and social skills intervention. Play and Social Skills for Children with Autism Spectrum Disorder is a must-have resource for researchers, clinicians, and graduate students in clinical child and school psychology, behavioral therapy/rehabilitation, social work, public health, and related psychology, education, and behavioral health fields.